DO EXECUTIVE WOMEN AVOID FINANCIAL PROBLEMS? - Silva, Fabiano Ferreira da; De Moura, André Aroldo Freitas (Advances in Scientific and Applied Accounting, 2022)
Purpose: This study investigates whether women in top management positions decrease the likelihood of financial problems. Method: The company's sample comprises Brazilian companies listed on B3, from 2010 to 2018. Altman's (1979) financial problems prediction model was used, and thus the variables of interest related to diversity were regressed of gender in senior management positions via the econometric logit model. To ensure robust results, a recent technique was used to balance companies that had women in top management with their peers via PSM and entropy. Results: We find that women avoid financial problems only when women take over as chairman of the company board two years before the company experiences financial problems. Contributions: To better understand how gender diversity can contribute to the management of Brazilian companies, mostly family companies or with high shareholding concentration, in situations of crisis and financial difficulties, given the recurrent political and health crises that impacted the Brazilian economy in this last decade.